21 Left atrial remodelling following treatment of symptomatic severe aortic stenosis. (26th April 2015) - Musa, TA; Uddin, A; Fairbairn, TA; Dobson, LE; Steadman, C; Kidambi, A; Motwani, M; Ripley, DP; McDiarmid, AK; Swoboda, P; Erhayiem, B; Garg, P; et al.
Abstract : Background: Left atrial (LA) size is an adverse prognostic marker. Aortic stenosis results in increased filling pressures with progressive left atrial enlargement and dysfunction. Intervention for aortic stenosis results in LV reverse remodelling, however the effect of TAVI or SAVR upon LA function remains poorly understood and the two treatments have not been directly compared. Aim: We assessed LA size and function in patients with severe symptomatic aortic stenosis before and 6 months TAVI and SAVR. Methods: All patients underwent an identical 1.5T CMR protocol and were in sinus rhythm at time of imaging. LA volumes were derived using the biplane area–length method (Figure 1 ). The total LA emptying fraction was derived as: (LAVmax–LAVmin)*100/LAVmax. Results: 23 SAVR patients (age 72.7 ± 7.5 years, 83% male, EuroSCORE II 1.40 ± 1.11%) and 23 TAVI patients (age 80.7 ± 6.9 years, 57% male, EuroSCORE II 4.99 ± 2.97%). The left atria of the TAVI group were significantly more dilated at baseline than those of the SAVR group (p = 0.039) however both groups were comparable at 6 months (p = 0.227). Similarly, the LA emptying fraction of the TAVI group was significantly lower than the SAVR group at baseline (p = 0.003) with comparable function seen at 6 months (p = 0.08) (Table 1). Conclusions: TAVI, but not SAVR, was associated with a significant reduction in LA volume and concomitant improvement in emptying fraction at 6 months. These preliminary findings may reflect worse LA function at baseline in the TAVI group or improved valvular haemodynamics with TAVI compared to SAVR.